Cyber-Buddhism and Changing Urban Space in Thailand - Taylor, Jim (Space and Culture, 2003)
Buddhism in Thailand has long been seen as a holistic cultural system, with an all-embracing normative cosmology that provides everyday meaning. However, it is also a diverse cultural system that produces alternative or Other counterstatist practices that have at times contested the power of the politico-administrative center. In this changing milieu, cyber-Buddhism has emerged as a response to the needs of an increasingly mobile, simulated, and fragmented transnational urban social order. Here, multiple sites essentially constitute the new (post-) metropolis and where material spatial practices and social arrangements have been recoded. This has affected the social practices of everyday life. The monasteries, the spiritual heart/center of the community, once the prime loci (and place) of much social activities and civic interests, now stand in the new middleclass imagination as icons of the past as a consequence of unfettered urban capitalism and the space of flows since the postwar years. Nevertheless, arising from the Thai experience with modernity are new spatial possibilities engendered in large part by hypertechnologies, especially the Internet; digitalized electronics potentially and markedly transforming religious space. In the privileging of space over many temporal (place-made) coordinates, human communities are left only with nostalgia and a simulated more real than real world where original, first-order things cease to exist. Perhaps now we are just beginning to realize the transformative possibilities in urban religion brought about by electronic space.